Share Prices and Total Shares Before and After Covid-19 Announcement in Consumer Goods Industry - An Suci Azzahra; Ayu Wirdha Ningsih; Prana Ugiana Gio (CV. AFDIFAL MAJU BERKAH, 2022)
This research aimed to analyze the reaction of stock prices and the total shares before and after the announcement of the covid-19 in the Consumer Goods Industry Sector on the Indonesia Stock Exchange. Research methodology: Data were acquired from the website www.idx.co.id with the sample of 50 companies. The observation period was at 31 January and 31 March 2020. The method research was a comparative study. Data were analyzed through the Wilcoxon Signed Rank Test. Results: The results showed that the announcement of covid-19 had an effect on stock prices as seen from the value (2-tailed) is 0.000 < 0.05. Meanwhile, the Covid-19 announcement did not affect the total shares, as seen from the value (2-tailed) is 0.490 > 0.05. Limitations: This research only observed one research object. The observation period was at 31 January and 31 March 2020. That is only examined 1 company sector, besides, it only compared two variables. Contribution: The companies must change their sales strategy to be able to raise stock prices and Total Shares.